Cadherin Trafficking for Tissue Morphogenesis: Control and Consequences. - West, J.J.; Harris, T.J. (Traffic, 2016)
Cadherin-based adherens junctions are critical for connecting cells in tissues. Regulated cadherin trafficking also makes these complexes amazingly dynamic, with permissive and instructive consequences on multicellular development. Here, we review how cadherin trafficking affects various forms of tissue morphogenesis from Drosophila and Caenorhabditis elegans to zebrafish, Xenopus and mouse. We describe how core trafficking machinery (such as clathrin, dynamin, Rab small G proteins and the exocyst complex) integrates with other molecular systems (transcriptional factors, signaling pathways, microtubules, actin networks, apico-basal polarity proteins and planar cell polarity proteins) to control cadherin endocytosis, exocytosis and recycling. This control can occur at all cell-cell contacts or specific junctions for distinct effects on tissue morphogenesis during animal development.